Impact of Inappropriate Antibiotic Therapy in Vancomycin-Resistant Enterococcus Bacteremia. (July 2021) - Aslam, Waqas; Mathew, Naomi E.; Shaver, Courtney; Brito, Veronica; Jones, Shirley; Arroliga, Alejandro C.; Ghamande, Shekhar
Abstract : Background: Vancomycin-resistant Enterococcus (VRE) bacteremia has significant morbidity and mortality. Empiric antibiotic regimens for treating patients with risk factors for multidrug-resistant organisms may not have medications directed at treating VRE. Study Question: To evaluate the impact of antibiotic therapy (and other risk factors) on mortality in VRE bacteremia. Study Design: We identified 146 patients with VRE bacteremia, admitted at our institution over an 11 years period (2004–2014). All inpatients with an initial positive VRE blood culture were included only once in the analysis. Eighteen patients were excluded from the study because of inability to retrieve medical information regarding one or more important study variables. The retrospectively collected data from electronic medical records of 128 patients were analyzed. Results: The inpatient, 30-day, and 1-year mortality rates from VRE bacteremia were 23%, 31%, and 59%, respectively. Only 19% patients were discharged home. Inappropriate antibiotics were prescribed in 19% patients. Appropriate antibiotics were prescribed in 81% patients (62% daptomycin and 37% linezolid); however, only 58% patients received appropriate antibiotics within 24 hours of the reported positive blood cultures. The 30-day and 1-year mortality rates for patients treated with inappropriate antibiotics were 54% and 67% compared with 26% and 50%, respectively, for those treated with appropriate antibiotics. The median survival rate for patients treated with inappropriate antibiotics was 1 month (95% confidence interval: 0.0–1.0) compared with 11 months (95% confidence interval: 4.0–13.0) for those treated with appropriate antibiotics. The advanced patient age (median age 75 years vs. 63 years) was a significant risk factor for inappropriate antibiotic therapy ( P value = 0.02). The multivariate Cox regression model revealed inappropriate antibiotic therapy ( P value = 0.003), septic shock ( P value = 0.0004), albumin ( P value = 0.04), and dementia ( P value = 0.003) to be associated with 30-day mortality. Conclusions: Our study highlights the detrimental effect of inappropriate antibiotic therapy and other risk factors on morbidity and mortality associated with VRE bacteremia.